Tinjauan Kebutuhan Geotextile pada Timbunan Tinggi di atas Tanah Lunak - Achmad Firman Maulana; Evandra Sebastian; Yerry Kahaditu Firmansyah (Pusat Riset dan Inovasi Nasional, 2025)
The process of embankment of the road body aims to create a safe and comfortable transportation route. However, the slopes on the road body often have limited stability and are susceptible to construction failure. The researcher intends to review the stability of the slope on the embankment with various variations in embankment height against the stability of embankment soil located on soft soil with a fairly deep depth. The need for geotextile reinforcement is influenced by the condition of the base soil itself. In geotextiles with the same Tult, the Tult of geotextiles used for all variations of embankment height in this study is 50 kN. The need for the number of geotextiles with the same embankment width and different variations in embankment height, the higher the embankment, the more geotextiles are needed.